EFFECT OF SALINITY ON PIGMENT CONCENTRATIONS OF SOME TROPICAL PHYTOPLANKTERS - Bhattathiri, P M A; Devassy, V P (Indian Journal of Fisheries, 2011)
Estuaries are characterised by marked diurnal and seasonal changes in salinity. These changes are brought about either by the tidal variations or by the infltix of freshwater from rivers and land runoff caused by the monsoon systan. As a result, the organisms inhabitiing the estuaries have to adapt themsdves to wide changes in salinity